Return to play after treating acute muscle injuries in elite football players with radial extracorporeal shock wave therapy - Morgan, James P.M.; Hamm, Mario; Schmitz, Christoph; Brem, Matthias H. (Journal of Orthopaedic Surgery and Research, 2021)
Background: To compare lay-off times achieved by treating acute muscle injuries in elite football players with a multimodal therapy approach that includes a specific protocol of almost daily radial extracorporeal shock wave therapy (rESWT) with corresponding data reported in the literature. Methods: We performed a retrospective analysis of treatments and recovery times of muscle injuries suffered by the players of an elite football team competing in the first/second German Bundesliga during one of the previous seasons. Results: A total of 20 acute muscle injuries were diagnosed and treated in the aforementioned season, of which eight (40%) were diagnosed as Type 1a/muscular tightness injuries, five (25%) as Type 2b/muscle strain injuries, four (20%) as Type 3a/partial muscle tear injuries and three (15%) as contusions. All injuries were treated with the previously mentioned multimodal therapy approach. Compared with data reported by Ekstrand et al. (Br J Sports Med 47:769–774, 2013), lay-off times (median/mean) were shortened by 54% and 58%, respectively, in the case of Type 1a injuries, by 50% and 55%, respectively, in the case of Type 2b injuries as well as by 8% and 21%, respectively, in the case of Type 3a injuries. No adverse reactions were observed. Conclusions: Overall, the multimodal therapy approach investigated in this study is a safe and effective treatment approach for treating Type 1a and 2b acute muscle injuries amongst elite football players and may help to prevent more severe, structural muscle injuries.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Acute muscle injury; Athletes; Extracorporeal shock wave therapy; Rehabilitation; Return-to-play